Meningkatkan Kemampuan Motorik Halus pada Anak Usia 4-5 Tahun melalui Media Busy Board - khasanah, Eni; Ramdani, Luthfi Aji (Al-DYAS, 2026)
Although early childhood fine motor development has been widely studied, research that specifically examines the effectiveness of busy board media in classroom learning contexts remains limited. This study aimed to analyze the effectiveness of using busy board media in improving the fine motor skills of children aged 4–5 years at PAUD Gemilang Petir. The study employed a quantitative approach with a classroom action research design, involving 28 children selected through purposive sampling. Data were collected using observation sheets that included indicators of cutting, pasting, and threading beads, and were analyzed descriptively. The results showed an increase in the percentage of fine motor skills from 54% at the initial observation to 75% in Cycle I and 92% in Cycle II, accompanied by an increase in the mean score to the Very Well Developed category. These findings confirm that the use of busy board media is effective in strengthening manipulative learning and providing optimal fine motor stimulation for young children. In conclusion, busy board media need to be used continuously by teachers as an interactive learning tool that supports fine motor development, while future research can broaden the subjects and compare busy boards with similar media to enrich the empirical evidence.